2020
DOI: 10.1055/a-1164-8152
|View full text |Cite
|
Sign up to set email alerts
|

Wild Strawberry, Blackberry, and Blueberry Leaf Extracts Alleviate Starch-Induced Hyperglycemia in Prediabetic and Diabetic Mice

Abstract: Intestinal α-glucosidase and α-amylase break down nutritional poly- and oligosaccharides to monosaccharides and their activity significantly contributes to postprandial hyperglycemia. Competitive inhibitors of these enzymes, such as acarbose, are effective antidiabetic drugs, but have unpleasant side effects. In our ethnopharmacology inspired investigations, we found that wild strawberry (Fragaria vesca), blackberry (Rubus fruticosus), and European blueberry (Vaccinium myrtillus) leaf extracts inhibit α-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…In a rat animal model, the efficacy of the aqueous extract of VM leaves in reducing a rise in blood glucose following starch consumption was observed in both obese rats and those with prediabetes or streptozocin-induced diabetes, the efficacy of the extract being comparable to that of acarbose [ 37 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…In a rat animal model, the efficacy of the aqueous extract of VM leaves in reducing a rise in blood glucose following starch consumption was observed in both obese rats and those with prediabetes or streptozocin-induced diabetes, the efficacy of the extract being comparable to that of acarbose [ 37 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Poly- and oligosaccharides are converted into monosaccharides by the action of intestinal α-glucosidase and α-amylase, and the activity significantly contributes to postprandial hyperglycemia. Synthetic agents such as acarbose can inhibit these enzymes, but the side effects, such as diarrhea, flatulence, and stomach pain, make them unsuitable [ 41 ]. The present study was designed to develop antidiabetics from natural products based on this strategy with lesser side effects [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme α-amylase and α-glucosidase activity were inhibited by ellagic acid or derivatives in aqueous fruit extract of Fragaria × a nanassa [ 26 ]. Similarly, another specie F. vesca leaf extract was reported to inhibit α-glucosidase and α-amylase enzyme activity [ 41 ]. Flavonoids in n -butanol extract of F. nilgerrensis Schlecht produced an antidiabetic effect [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study on diabetic GK rats the bilberry leaf decoction lowered the occasional glycaemia ( Ferreira et al, 2010 ) and, in a similar study, blood glucose level and glycated hemoglobin returned to normal in 50% of the diabetic rats ( Sidorova et al, 2017 ). A study on prediabetic and diabetic mice showed that the extract from bilberry leaves inhibits α -glucosidase and α -amylase enzyme activity and prevents postprandial hyperglycaemia by slowing down the rate of saccharide digestion ( Takács et al, 2020 ). The α-glucosidase inhibitory activity of the applied bilberry leaf extract was found to be comparable to acarbose in an in vitro experiment ( Bljajić et al, 2017 ).…”
Section: Uses Of Vaccinium Myrtillus Lmentioning
confidence: 99%